Diallyl Disulfide From Garlic Oil Inhibits Pseudomonas aeruginosa Quorum Sensing Systems and Corresponding Virulence Factors - Li, Wen-Ru; Ma, Yong-Kai; Xie, Xiao-Bao; Shi, Qing-Shan; Wen, Xia; Sun, Ting-Li; Peng, Hong (Frontiers in Microbiology, 2019)
Previously, we determined that diallyl disulfide (DADS) from garlic oil can inhibit Pseudomonas aeruginosa PAO1 pathogenic factors by inactivating the transcription of key genes from three quorum sensing (QS) systems (las, rhl, and pqs) based on the effects of DADS on growth, virulence factor production (elastase, pyocyanin, biofilm, and swarming motility), and RNA transcription (real-time q-PCR). To further investigate the mechanisms underlying the inhibition of the three P. aeruginosa QS systems by DADS, high-throughput RNA and proteome sequencing techniques were used to study differences in the transcriptional and proteome expression of P. aeruginosa PAO1 following treatment with DADS. The RNA-seq and proteomic data are available via NCBI Gene Expression Omnibus database with accession number GSE118801 and ProteomeXchange with identifier PXD011144, respectively. The experimental results indicated that all key genes of the three QS systems (las, rhl, and pqs) of P. aeruginosa PAO1 as well as the virulence factors (including exoprotease LasA, elastase LasB, lectin LecA and LecB, pyocyanin biosynthesis, and biofilm formation) regulated by these three QS systems were inhibited. This is consistent with our previous studies on the physiology, biochemistry, and RNA expression of P. aeruginosa treated with DADS. Additionally, our results also indicated that bacterial motility, chemotaxis, and two-component systems were inhibited by DADS treatment. All these changes abolish the sensitivity of P. aeruginosa PAO1 to environmental stimuli and cause the cells to be in a state of passivation. Further research is needed to determine how QS systems regulate these functions. Our findings could potentially contribute to the treatment and control of P. aeruginosa infection, virulence, and pathogenicity.